Crystallization of Santeri's Religious Attitudes through the Boarding Cultural Process - Mahlil Nurul Ihsan; Nurwadjah Ahmad; Aan Hasanah; Andewi Suhartini (Journal of Social Science, 2021)
Each Boarding culture has a unique variation in shaping the religious attitudes of students. This problem was initially caused by the weakness of the Boarding culture, which caused the moral decadence of students so that the process of Boarding culture had to be strengthened. This type of research uses qualitative field research with descriptive methods and data collection techniques using interviews, documentation, and observation. This study explains the cultural process of the modern Al-Aqsho Islamic boarding school, Sumedang Regency, consisting of religious socialization, modernity, moderation, adaptation emphasizing modern life systems, habituation which is applied more to the habituation of the grantor system, and enculturation showing modern Boarding culture. Meanwhile, the cultural process of Al-Ittifaq Islamic Boarding School in Bandung Regency consists of religious socialization, entrepreneurship, and society, adaptation emphasizing the adaptation of spiritual experiences, adaptation highlighting the social life system of the community, adaptation to the entrepreneurial work environment, habituation applied to the religious method, community and entrepreneurship and enculturation shown religious agribusiness Boarding culture.